2015
DOI: 10.1039/c5cc06921a
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-oriented synthesis of tetrathia[8]circulenes by sequential C–H borylation and annulation

Abstract: We have succeeded in the diversity-oriented synthesis of tetrathia[8]circulenes by sequential C-H borylation and annulation from cyclic tetrathiophene, and time-resolved microwave conductivity studies have proved that the intrinsic hole mobilities of tetrathia[8]circulenes are dependent on the chain length of the alkyl substituents at the peripheral positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 37 publications
1
67
0
Order By: Relevance
“…We found that the simulated absorption spectrum was consistent with the experimental one (Figures a and S5 in the Supporting Information), and these results clearly suggest that the lowest energy band of 1 a at 350–400 nm has a symmetry forbidden nature (Figure a and Table S3 in the Supporting Information) . In sharp contrast, we have previously reported that the lowest‐energy absorption bands in tetrathia[8]circulenes were observed in the 350–450 nm region . The significant change in the absorption spectra of 1 and tetrathia[8]circulenes is considered to be caused by the difference of the symmetric feature and the annulation modes.…”
Section: Methodsmentioning
confidence: 69%
See 3 more Smart Citations
“…We found that the simulated absorption spectrum was consistent with the experimental one (Figures a and S5 in the Supporting Information), and these results clearly suggest that the lowest energy band of 1 a at 350–400 nm has a symmetry forbidden nature (Figure a and Table S3 in the Supporting Information) . In sharp contrast, we have previously reported that the lowest‐energy absorption bands in tetrathia[8]circulenes were observed in the 350–450 nm region . The significant change in the absorption spectra of 1 and tetrathia[8]circulenes is considered to be caused by the difference of the symmetric feature and the annulation modes.…”
Section: Methodsmentioning
confidence: 69%
“…For example, tetraoxa[8]circulenes, diazadioxa[8]circulenes, and tetrabenzotetraaza[8]circulene have been successfully prepared as core frameworks incorporating four benzene rings with four heteroaromatic rings (Scheme ). Very recently, Wong's group and we have independently reported the synthesis of tetrathia[8]circulenes and tetraselena[8]circulene …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…in 2013; in the solid state 1 was found to have a saddle‐shaped conformation. In contrast, hetero[8]circulenes such as oxa[8]circulene 2 , thia[8]circulene 3 ,, and selena[8]circulene 4 have been prepared and found to display rather planar structures. We have recently reported a “fold‐in”‐type oxidative synthesis of tetrabenzotetraaza[8]circulene AC , which displays a quite planar structure and sharp absorption and emission spectra characteristic of polycyclic aromatic hydrocarbons .…”
Section: Methodsmentioning
confidence: 99%